The Relationship between Students' Self-esteem and Parental Attitudes in Turkish Society - Ersoy, Evren; Ugur, Hasan (KAMLA-RAJ ENTERPRISES, 2015)
The purpose of this study is to investigate the relationship between middle school students' self-esteem and their perceived parental attitudes. This study follows a screening model, which utilizes the scales that measures the students' perception of parental attitudes and self-esteem. This study was conducted on students in nine public middle schools in Istanbul during the 2012-2013 academic year. The Pearson product-moment correlation coefficient was utilized for data analysis. The results indicate that students mostly perceive their parents' attitudes as democratic.. Moreover, it was observed, that students had high self-esteem. As the democratic attitude, which is one of the sub-dimensions of parental attitudes, increases, a student's self-esteem also increases.. However, when the parents' protective demanding and authoritarian attitudes increase, a student's self-esteem decreases.
Keywords: Middle School; Adolescence; Quantitative Study; Self-esteem; Turkey; BEHAVIOR PROBLEMS; CHILDREN; STRESS; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics